Effect of pressure on the flow behavior of polybutene - Ponjavic,A; di,Mare L; Wong,J (Journal of Polymer Science Part B: Polymer Physics, 2014)
The rheology of submicron thick polymer melt is examined under high normal pressure conditions by a recently developed photobleachedfluorescence imaging velocimetry technique. In particular, the validity and limitation of Reynold equation solution, which suggests a linear throughthickness velocity profile, is investigated. Polybutene (PB) is sheared between two surfaces in a point contact. The results presented in this work suggest the existence of a critical pressure below which the throughthickness velocity profile is close to linear. At higher pressures however, the profile assumes a sigmoidal shape resembling partial plug flow. The departure of the sigmoidal profile from the linear profile increases with pressure, which is indicative of a secondorder phase/glass transition. The nature of the transition is confirmed independently by examining the pressuredependent dynamics of PB squeeze films. The critical pressure for flow profile transition varies with molecular weight, which is consistent with the pressureinduced glass transition of polymer melt.